An in-Depth Analysis of the Swelling, Mechanical, Electrical, and Drug Release Properties of Agar–Gelatin Co-Hydrogels. Issue 6 (13th April 2017) - Pandey, Preeti Madhuri; Nayak, Suraj K.; Shaw, Gauri Shankar; Uvanesh, K.; Banerjee, I.; Al-Zahrani, S. M.; Anis, Arfat; Pal, Kunal
ABSTRACT: Agar–gelatin-based co-hydrogels were prepared with different compositions of the agar and the gelatin fractions. The intermolecular hydrogen bonding was higher in the co-hydrogels as compared to the gelatin hydrogel. Swelling studies indicated diffusion-mediated swelling. The electrical stability of the co-hydrogels was higher as compared to the gelatin hydrogel. Though the firmness of the co-hydrogels was higher, Weichert model of viscoelasticity indicated that the inherent mechanical stability of the gelatin hydrogel was superior. The release of ciprofloxacin hydrochloride was predominately Fickian diffusion-mediated. In gist, the co-hydrogels can be tried as polymeric constructs for controlled drug delivery applications. GRAPHICAL ABSTRACT: